2014
DOI: 10.3748/wjg.v20.i45.17141
|View full text |Cite
|
Sign up to set email alerts
|

Appropriate treatment strategies improve survival of hepatocellular carcinoma patients with portal vein tumor thrombus

Abstract: Surgical resection is the most effective therapeutic strategy for HCC patients with PVTT and results in high hepatic functional reserve. For patients who can tolerate the procedure, postoperative TACE is necessary to prevent recurrence and prolong the survival period.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
66
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 47 publications
(68 citation statements)
references
References 24 publications
1
66
1
Order By: Relevance
“…Only a few studies have classified PVTT according to its extent. In the literature, classification of the extent of PVTT is heterogeneous, and most studies primarily investigated different treatment options, such as transarterial chemoembolization (TACE), radioembolization, resection, radiotherapy or systemic therapy . Only a few of these studies include a detailed classification of PVTT into several subgroups as suggested by Cheng et al or by the Liver Cancer Study Group of Japan .…”
Section: Introductionmentioning
confidence: 99%
“…Only a few studies have classified PVTT according to its extent. In the literature, classification of the extent of PVTT is heterogeneous, and most studies primarily investigated different treatment options, such as transarterial chemoembolization (TACE), radioembolization, resection, radiotherapy or systemic therapy . Only a few of these studies include a detailed classification of PVTT into several subgroups as suggested by Cheng et al or by the Liver Cancer Study Group of Japan .…”
Section: Introductionmentioning
confidence: 99%
“…In addition to stage B, treatment option for stage C patients was challenged as well. Numerous studies, mostly from Asian countries, indicated that liver resection can be safe and effective in patients with HCC involving portal vein tumour thrombus . In China, nearly half of patients with primary HCC are diagnosed in an advanced stage .…”
Section: Discussionmentioning
confidence: 99%
“…Several studies have reported that perioperative treatment with hepatectomy could improve the prognosis of HCC patients with PVTT. Previous studies have reported the outcomes of combination treatment based on surgical resection for HCC patients with PVTT (Table ) . The MST and 1‐year OS rate after combination treatment ranged from 11.5 to 37 months and from 46.8% to 100%, respectively.…”
Section: Surgical Resection Combined With Multidisciplinary Treatmentmentioning
confidence: 99%
“…The surgical mortality rate in patients with PVTT who receive surgical resection ranges from 0% to 10% (Table ) . It should be noted that patients who receive surgery are usually carefully selected.…”
Section: Surgical Indications and Procedures For Hcc With Pvttmentioning
confidence: 99%
See 1 more Smart Citation